483 Regional Review of Paediatric Radioallergosorbent Tests® (Rast) over 5 Years in Ireland: an Epidemiological Study in a Defined Birth Cohort. (October 2012) - Feeney, N; Barrett, N; Philip, RK
Abstract : Background and Aims: RAST and related in-vitro tests assist in diagnosing childhood allergies. Aims: 1. To analyse paediatric RAST results and determine local prevalence of sensitivities, 2. To develop guidelines towards recetly introduced ImmunoCAP® test panel selection incorporating local sensitivity prevalence in Ireland. Methods: RAST requests from 0–16 year population in Mid-West of Ireland were analysed between January 2004 to February 2009, excluding those not born in the Regional Maternity Hospital, to gain true birth cohort reflection of sensitivity patterns. Both total and allergen specific IgE levels were tabulated. Results: Total of 3033 successful sample requests for RAST (Immulite 2000) during the 62 month study period qualified for analysis. Standardised classification system for allergen specific allergy levels showed mean total IgE of study population at 314.75 kU/L and median of 52kU/L (expected elevated levels in a possible symptomatic patient sample). 76.8% of tests originated in hospitals and 23.2% from primary care. Most commonly tested allergen was house dust mite (1595) followed by Timothy grass (1155) and at 3 rd place food panel 5 comprising egg white, milk, cod fish, wheat, peanut & soya bean. With standardised cut-off levels high and very high levels were noted frequently for egg 5.5%, dust mite 19%, timothy grass 14% followed by Horse, Cat and Dog. Our ImmunoCAP test guidelines incorporated information from RAST audit. Conclusion: Our paediatric RAST analysis provided regional allergen specific sensitivity pattern in Ireland thus assist ing clinicians in choosing appropriate allergens to be requested thus reducing cost and enhancing clinical relevance.